The Role of Internal Control in Combating Corruption in the Procurement Units in the Palestinian Public Sector Institutions - Swaitti, Shibly (The Arab Journal of Administration, 2022)
Abstract: The study aims at shedding light on the role of internal control (in procurement units) in combating corruption in Palestinian public sector institutions. In conducting the study, the descriptive methodology was used due to its suitability for study. An online questionnaire that was especially prepared for the purpose of this study was prepared, in accordance with the Likert 5-points scale. It consisted on (40) items and was distributed to (94) heads of procurement units, who represent (15) procurement units in the ministries and governmental organizations in the cities of Ramallah and Al-Bireh. All items were analyzed using the SPSS program. The study concluded that internal control is applied to a high degree in its different dimensions (control environment, risk assessment, control activities, information and communication, supervisory follow-up) in procurement units at the Palestinian public sector institutions, and the value of the total arithmetic mean is (3.91), and the overall level of anti-corruption (in procurement units) in Palestinian public sector institutions came out at a high level with a mean of (4.01). The study concluded that there is a statistically significant effect for internal control in procurement departments in promoting the fight against corruption from the point of view of the employees of the procurement units in the Palestinian public sector institutions. The study recommends the necessity of urging senior administrations in the Palestinian public sector institutions to give the necessary attention to the issue of internal control over the information and communication technology used in the procurement units in it, and to set standards and control procedures for the process of detecting unauthorized access to information in approved computer programs, and to reconsider the regulations related to administrative and financial penalties for cases of corruption that are discovered in these departments.